Surgery for Massive Paediatric Head and Neck Neurofibroma: Two Case Reports - ZA, Asha’ari; A, Kahairi; H, Shahid (IIUM Medical Journal Malaysia, 2012)
We report two paediatric patients with massive head and neck plexiform neurofibromas who underwent surgical excision. We wish to highlight issues and implications pertaining to the surgery, in particular, the management of intraoperative bleeding often encountered in these cases.